Hydrological variations in the Yellow River Source area (NE Tibetan Plateau) during the last 7.4 ka inferred from stable isotopes of ostracod valves - Meijiao Chen; Fang Tian; Xianyong Cao; Wanyi Zhang; Birgit Plessen; Steffen Mischke (CATENA, 2023)

Large‐scale mass movements recorded in the sediments of Lake Hallstatt (Austria)–evidence for recurrent natural hazards at a UNESCO World Heritage site - Stefan Lauterbach; Michael Strasser; Kerstin Kowarik; Hans Reschreiter; Gerhard W. Mandl; Christoph Spötl; Birgit Plessen; Achim Brauer (Journal of Quaternary Science, 2023)
The Bronze to Iron Age underground salt mining complex of Hallstatt (Austria) is widely recognised for its cultural importance and wealth of archaeological artefacts. However, while the daily life in the salt mines is archaeologically well documented and environmental effects of the mining activity have been investigated recently, the impact of natural hazards on the prehistoric mining community is still poorly understood. For instance, while it is well established that the prehistoric underground mines have repeatedly been destroyed by large‐scale mass movements, only little is known about the characteristics and extent of these events as well as about mass‐movement recurrence during more recent times. To shed light on past mass‐movement activity in the vicinity of the Hallstatt salt mines, we investigated sediment cores from adjacent Lake Hallstatt. Within the regular lake sediments we identified three large‐scale event deposits, which are interpreted to originate from spontaneous or seismically induced mass movements in the mid‐19th and late 9th century ce and the mid‐4th century bce. While the age of the latter event is in good agreement with the abandonment of the famous Iron Age cemetery at Hallstatt, the younger events indicate that large‐scale mass movements also occurred repeatedly during the Common Era.

Late glacial and Holocene climate in the Kunlun Pass region (northern Tibetan Plateau) inferred from a multi-proxy lake record - Wanyi Zhang; Steffen Mischke; Dominic Hosner; Chengjun Zhang; Birgit Plessen; Huwei Li; Xiaojing Zhang (Quaternary International, 2023)

Hypolimnetic oxygen conditions influence varve preservation and δ13C of sediment organic matter in Lake Tiefer See, NE Germany - Nadine Dräger; Birgit Plessen; Ulrike Kienel; Michał Słowiński; Arne Ramisch; Rik Tjallingii; Sylvia Pinkerneil; Achim Brauer (Journal of Paleolimnology, 2019)

Aquatic macrophyte dynamics in Lake Karakul (Eastern Pamir) over the last 29 cal ka revealed by sedimentary ancient DNA and geochemical analyses of macrofossil remains - Liv Heinecke; Laura S. Epp; Maria Reschke; Kathleen R. Stoof-Leichsenring; Steffen Mischke; Birgit Plessen; Ulrike Herzschuh (Journal of Paleolimnology, 2017)

Climatic and limnological changes at Lake Karakul (Tajikistan) during the last ~29 cal ka - Liv Heinecke; Steffen Mischke; Karsten Adler; Anja Barth; Boris K. Biskaborn; Birgit Plessen; Ingmar Nitze; Gerhard Kuhn; Ilhomjon Rajabov; Ulrike Herzschuh (Journal of Paleolimnology, 2017)

Effects of spring warming and mixing duration on diatom deposition in deep Tiefer See, NE Germany - Ulrike Kienel; Georgiy Kirillin; Brian Brademann; Birgit Plessen; Reinhard Lampe; Achim Brauer (Journal of Paleolimnology, 2017)

Different carbon reservoirs of auriferous fluids in African Archean and Proterozoic gold deposits? Constraints from stable carbon isotopic compositions of quartz-hosted CO2-rich fluid inclusions - Volker Lüders; Reiner Klemd; Thomas Oberthür; Birgit Plessen (Mineralium Deposita, 2015)

Modern seasonality in Lake Challa (Kenya/Tanzania) and its sedimentary documentation in recent lake sediments - Christian Wolff; Iris Kristen-Jenny; Georg Schettler; Birgit Plessen; Hanno Meyer; Peter Dulski; Rudolf Naumann; Achim Brauer; Dirk Verschuren; Gerald H. Haug (Limnology and Oceanography, 2014)
From November 2006 to January 2010, a sediment trap that was cleared monthly was deployed in Lake Challa, a deep stratified freshwater lake on the eastern slope of Mt. Kilimanjaro in southern Kenya. Geochemical data from sediment trap samples were compared with a broad range of limnological and meteorological parameters to characterize the effect of single parameters on productivity and sedimentation processes in the crater basin. During the southern hemisphere summer (November—March), when the water temperature is high and the lake is biologically productive (nondiatom algae), calcite predominated in the sediment trap samples. During the “long rain” season (March—May) a small amount of organic matter and lithogenic material caused by rainfall appeared. This was followed by the cool and windy months of the southern hemisphere winter (June—October) when diatoms were the main component, indicating a diatom bloom initiated by improvement of nutrient availability related to upwelling processes. The sediment trap data support the hypothesis that the light—dark lamination couplets, which are abundant in Lake Challa cores, reflect seasonal delivery to the sediments of diatom‐rich particulates during the windy months and diatom‐poor material during the wet season. However, interannual and spatial variability in upwelling and productivity patterns, as well as El Niño—Southern Oscillation (ENSO)‐related rainfall and drought cycles, exert a strong influence on the magnitude and geochemical composition of particle export to the hypolimnion of Lake Challa.

Using variations in the stable carbon isotope composition of macrophyte remains to quantify nutrient dynamics in lakes - Ulrike Herzschuh; Steffen Mischke; Hanno Meyer; Birgit Plessen; Chengjun Zhang (Journal of Paleolimnology, 2010)

Effects of detrital carbonate on stable oxygen and carbon isotope data from varved sediments of the interglacial Piànico palaeolake (Southern Alps, Italy) - Clara Mangili; Achim Brauer; Birgit Plessen; Peter Dulski; Andrea Moscariello; Rudolf Naumann (Journal of Quaternary Science, 2010)
Contamination with detrital matter is a well‐known bias in δ 18 O records from lake carbonates but quantitative information of this effect is yet lacking. Therefore, we developed a new methodological approach combining isotope analyses with microfacies, X‐ray diffraction and micro‐X‐ray fluorescence data and applied this in a case study for the Piànico interglacial lake record in order to provide a quantitative estimate of the effect of detrital carbonate on stable δ 18 O and δ 13 C data. The Piànico record contains a long series of distinct and well‐preserved calcite varves and is correlated to Marine Isotope Stage 11. Intercalated in the varve sequence are detrital layers triggered by surface erosion events. These detrital layers are mainly composed of dolomite, thus reflecting the mineralogical signature of the catchment. Microfacies analyses of a 9350 varve year interval allows the identification of detrital layers down to sub‐millimetre scale and a precise selection of three different types of samples for isotope analyses: (1) pure endogenic calcite varves (five varves per sample) without detrital contamination; (2) individual detrital layers; and (3) ‘mixed’ samples including five calcite varves and up to four thin detrital layers. Detrital samples show the isotopic signature of the catchment dolomite and are up to 5.7‰ enriched in δ 18 O values with respect to endogenic calcite samples. In mixed samples, the degree of isotopic enrichment is directly related to the amount of detrital contamination; δ 18 O of bulk carbonates is significantly biased when the detrital component amounts to more than 5% of the sample. It is also shown that samples containing detrital material have an influence on the calculation of the covariance between δ 13 C and δ 18 O. Covariance is high ( r = 0.76) when the correlation coefficient is calculated on the base of all samples, but absent ( r = −0.43) when samples containing detrital dolomite are excluded. It has been demonstrated that microfacies analysis is a quick tool to avoid or reduce detrital contamination in bulk carbonate samples during sample selection. Copyright © 2009 John Wiley & Sons, Ltd.

Magnetic properties and environmental changes recorded in Lake Lehmilampi (Finland) during the Holocene - Eeva Haltia-Hovi; Norbert Nowaczyk; Timo Saarinen; Birgit Plessen (Journal of Paleolimnology, 2010)

Evaporation effects as reflected in freshwaters and ostracod calcite from modern environments in Central and Northeast Yakutia (East Siberia, Russia) - Sebastian Wetterich; Ulrike Herzschuh; Hanno Meyer; Lyudmila Pestryakova; Birgit Plessen; C. M. Larry Lopez; Lutz Schirrmeister (Hydrobiologia, 2008)